ELECTROCHEMICAL BEHAVIOUR OF THE NEW HETEROCYCLIC PYRIDINIUM LIGANDS - CÂRÂC, Andreea; BOSCENCU, Rica; DINICĂ, Rodica Mihaela; CÂRÂC, Geta (Studia Universitatis Babeș-Bolyai Chemia, 2015)
New heterocyclic pyridinium compounds as N,N’ di-(p-bromophenacyl)-4,4’-bipyridinium dibromide (Lr) and N,N’ di-(p-bromophenacyl)-1,2-bis(4-pyridinium)-ethane dibromide (Lm) were investigated applying cyclic voltammetry to evaluate the electrochemical behaviour. The stability of new heterocyclic pyridinium compounds in aquatic media depends on pH and the dependence was correlated with spectrophotochemical data. The ethylenic group from Lm induces changes on the stability and on the electrochemical performances of the ligand. The quasireversible process on electron transfer between functional groups depends on pH and also on the scan rates of the potential applied. The alkaline pH of a media is more favorable than acidic pH for the ligand’s stability and the electron transfer process on platinum electrode. The study of the redox potential on the two ligands indicates the role as mediator candidate in the reduction mechanism. We believe that the present work will stimulate the investigations of the chemical features of ligands and their role in biological and medicinal chemistry.